Impact Magazine (2021)
The fall semester is now well underway. Although the challenges of the pandemic are far from behind us, it is refreshing to see our beautiful campuses once again filled with students and flowing with renewed energy and excitement. CBSS continues to gain new students, more than a dozen new faculty members joined the college this Fall, and the college continues to make significant impacts on our communities through our instructional, scholarship, and community engagement activities. In short, the faculty, staff, and students in CBSS continue to push forward—in the face of obvious obstacles—toward our vision of being a recognized leader in creating safe, strong, and healthy communities. The support from friends and alumni of the college is key to the progress and success of our college. The ongoing legacy of Dr. Saba Jallow’s is a powerful example the multitude of ways the work of CBSS impacts individuals and communities. Across his career at Georgia Southern, Dr. Jallow was dedicated to teaching, research, and activism influenced by US and international politics, human rights, and the Black experience in the US and abroad. Among his numerous accomplishments and accolades described throughout this issue of IMPACT, Dr. Jallow was a constant and unrelenting champion for diversity and inclusion at Georgia Southern and across our communities. In addition to Dr. Jallow’s impressive and celebratory academic achievements, Dr. Jallow’s mentorship of students over the years has been particularly impactful. During my time as Dean, I have had the opportunity to meet with dozens of distinguished alumni who were mentored by Dr. Jallow, as well as his wife, Mrs. Renata Jallow. The stories of the profound influence that Dr. and Mrs. Jallow had on the students are very powerful and center on the incredible amount of time, love, and guidance that the couple provided to these students and countless others. Students mentored by Dr. and Mrs. Jallow have gone to make substantial impacts on their communities through careers and community involvement in law, politics, religion, art, activism, academics, and a variety of other important activities related to social justice. To honor Dr. Jallow’s longstanding and continued impact on Georgia Southern and our students, Attorney Francys Johnson (’01, CBSS Advisory Board) led the effort to create the Saba Jallow Legacy Fund: https://cbss.georgiasouthern.edu/dr-saba-jallow-legacy-fund/. This fund supports the Saba and Renata Jallow Race, Politics, and the African Diaspora film series, students in the Africana Studies Program through scholarships and financial assistance to attend the International Model Union Conference, and the Saba M. Jallow CBSS Inclusion Champion Award. Please consider supporting this effort that will ensure Dr. Jallow’s influence and legacy is honored and remains strong in his retirement.https://digitalcommons.georgiasouthern.edu/cbss-impact/1002/thumbnail.jp